Security trends for FPGAS from secured to secure reconfigurable systems (Springer, 2011)
This book is designed for all those who would like to upgrade their knowledge in the field of security and digital platforms including reconfigurable FPGAs.  It is the result of a national project (ICTER) funded by the French National Research Agency (ANR) and involving four research centers (Montpellier, Paris, Lorient, Saint-Etienne) and a private company. This book details several solutions for secure application execution and application update. It presents an analysis of current threats against embedded systems and especially FPGAs. The discussion includes requirements to build a secure system, according to the FIPS standard. New secure schemes are proposed to ensure data confidentiality, integrity and authentication.  These new schemes fit the tight requirements of embedded systems (performance, memory footprint, logic area and energy consumption). The cost of different architectures for performance, memory, and energy are estimated. Innovative solutions for remote reconfigurations are also detailed, taking into account security when downloading a new bitstream.  Since the replay of an old bitstream in the field is a major threat for embedded systems, this issue is discussed and an original solution proposed. Proposes solutions at the logical, architecture and system levels in order to provide a global solution Clearly defines the security boundaries for a system Describes different hierarchical levels of a design, from application to technological levels.